Determinants of Indonesian muslim consumers' willingness to pay for Taiwanese snacks: the role of the halal logo / Atika Nur Aini and Anya Safira - Safira, Anya; Nur Aini, Atika (Universiti Teknologi MARA, 2021)
Indonesia is a country that has enormous market potential in terms of the halal food industry. The government has been attracting foreign food manufacturers to venture into the country's market; this includes snacks from Taiwan, one of them being Shihlin Taiwan Street Snacks. The public has been highly critical of Shihlin's food products of late due to doubts about its halal status and compliance with halal standards in manufacturing and supply chain activities. The company responded to the public's concern by obtaining the Indonesian Ulema Council (MUI) halal certification, increasing prices and affecting consumers' willingness to pay. In the form of a case study, this research aims to analyse the factors that influence Muslim consumers' willingness to pay for Taiwanese snacks in Indonesia, specifically Shihlin Taiwan Street Snacks. A total of 326 Indonesian Muslims took part in our survey, which data was analysed using SmartPLS. The study results revealed that animal slaughter, halal logos, price consciousness, food quality, and religious commitment positively influence Muslim consumers' willingness to pay for the snacks. The findings can benefit halal food companies in formulating strategies to guarantee consistent compliance of the halal standards in the manufacturing processes. Besides, we urge halal food regulators to provide better clarity in developing the halal and tayyib food criteria to earn better trust and confidence from Muslim consumers.